In situ and invasive melanoma in a high‐risk, New Zealand, population: A population‐based study. (26th July 2018) - Elwood, J Mark; Kim, Stella J‐H; Ip, Ken H‐K; Oakley, Amanda; Rademaker, Marius
Abstract: Background: Few population‐based studies assess both invasive and in situ melanoma. We document all patients with a first biopsied melanoma in a general population in New Zealand (NZ). Methods: All residents in a defined area of New Zealand with a biopsy showing a new primary invasive or in situ melanoma from 2010 to 2012 were identified, 974 patients; analysis used multivariate methods. Results: Age‐standardised incidence rates were 34.3 in females (F) and 41.4 in males (M) for invasive, 20.9 F and 27.6 M for in situ, and 55.2 F and 69.0 M for total melanoma. More in situ melanoma occurred in older patients and on the head and neck. Geometric mean Breslow thickness for invasive was 0.78 mm F and 0.85 mm M, with thicker lesions at ages over 60 and on the lower limb; there was no significant relationship with sex, distance from care or social deprivation assessed from residential address. Nodular melanomas (15%) were more frequent in older and male patients, and on the limbs, and were thicker. The estimated cumulative risk for melanoma is 4.4% F and 4.6% M by age 70. The body site distribution and sex differences were consistent with sun exposure patterns. Estimated incidence of melanoma in New Zealand in 2018 is 2500 invasive and 1700 in situ cases. Conclusions: Assessing both in situ and invasive melanoma expands the clinical picture, better estimating health care demand and costs. Results suggest that in situ disease is a more slowly growing lesion than the early phase of invasive disease. The features of thicker or nodular melanoma show priorities for prevention and early detection.